(untitled) (Fiep Bulletin - online, 2015)
This study had as objective evaluates the palmar prehension strength in individuals of the masculine gender, bearers of mental deficiency with or without Down’s Syndrome with age between 20 and 40 years old and to correlate the data obtained with the normal population, seeking to indicate parameters, and a scale of force for bearers of Down’s Syndrome. It is a cross-sectional study design that counted with the participation of 110 individuals’, divided in three groups: Control Group (GC) = 40 (normal individuals), Group bearer of Down’s Syndrome (GSD) = 30 and the Group with Mental Deficiency not associated to syndrome (GDM) = 40. The prehension strength was verified with the JAMAR dynamometer. The GSD presented values significantly smaller than the GDM, both smaller in relation to the GC; the obtained data should be considered as indicative of strength for the training of the manual function of the bearer of Mental Deficiency and Bearer of Down’s Syndrome.